EFEKTIFITAS KONSUMSI AIR BENING DAN CARICA PAPAYA L SEBAGAI TERAPI ALAMIAH UNTUK MENGATASI KONSTIPASI - Nilawati Soputri (Jurnal Skolastik Keperawatan, 2021)
Introduction: Constipation can be caused by the lack of water intake. Continues constipation that is not treated can cause various health problems in the digestive system. The purpose of the study is to find out the effectiveness of drinking warm water in the morning before breakfast in treating constipation. Method: 25 participants volunteered to participate in this study. The subjects have a history of recurrent constipation in the last 3 months, had no defecated in the past 3 days at the time of the study, and had no urge to defecate. The subjects did not consume laxatives nor herbs to facilitate defecation. The subjects were given 500 cc of warm water before breakfast every day for three consecutive days. The effectiveness of therapy is measured by percentage of the subjects that can defecate on the first day, second day and the third day. Results: The result of the study shows that the therapy was 68% effective on the first day, 88% effective at the second day, and 84% effective on the third day of therapy. During the three days of intervention, 60% subjects can defecate every day and 96% subjects can defecate at least once in three days of the study. Based on this study warm water therapy can be used as an alternative way to overcome constipation. Discussion: Further studies are needed to evaluate the efficacy of the warm water with longer treatment period. A larger sample selection and treatment based on etiology are needed to be considered in future studies.